Substitusi Tepung Tapioka dengan Tepung Sorgum Putih (Sorghum bicolor L. Moench) terhadap Kualitas Sosis Itik Manila: Substitution Of Tapioca Flour With White Sorghum Flour (Sorghum bicolor L. Moench) On The Quality Of Manila Duck Sausage - Maria Elmince Un; Heri Armadianto; Pieter Rihi Kale (Universitas Nusa Cendana, 2023)
This study aims to determine the characteristics of Manila duck sausage added with white sorghum flour (shorghum bicolor L. Moench) as a partial substitute for tapioca flour on fat content, fat oxidation level, antioxidant content, color and taste of Manila duck sausage. The research design used a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment P0= tapioca flour 15% +0% white sorghum flour; P1= tapioca flour 10% + 5% white sorghum flour; P2 = tapioca flour 5% +10% white sorghum flour and P3 = tapioca flour 0% + 15% white sorghum flour. The results of the study statistically showed that the use of white sorghum flour as a partial substitute for tapioca flour had no significant effect (P>0.05) on the fat content but had a very significant effect (P<0.01) on the level of fat oxidation, the antioxidant content, color and taste of the starch. Manila duck sausage Conclusion replacing tapioca flour with white sorghum flour by 10-15% caused a decrease in the level of fat oxidation, while the fat content did not change and there was an increase in antioxidants in Manila duck sausage. Fat content values ​​ranged from 1.36 0.12 -1.81 0.27%, fat oxidation 5.98 ±0.79- 3,490.45 (mg.eq/kg), antioxidant 7.7242.53 36.66±1.54 %, color 5,000 - 1.83±0.91 and taste 2,000 - 2.97±0.77. From the aspect of organoleptic research, partial replacement of white sorghum flour with tapioca flour up to 15% causes the color of the sausage tochange to blackish gray and the taste of the sausage increases compared to the control.. Penelitian ini bertujuan untuk mengetahui karakteristik sosis itik Manila yang ditambahkan tepung sorgum putih (shorghum bicolor L. Moench) sebagai pengganti sebagian tepung tapioka terhadap kandungan lemak, tingkat oksidasi lemak, kandungan antioksidan, warna dan rasa sosis itik Manila. Rancangan penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan dan 3 ulangan. Perlakuan P0 = tepung tapioka 15% + 0% tepung sorghum putih; P1= tepung tapioka 10 % + 5% tepung sorghum putih; P2 = tepung tapioka 5% +10% Tepung sorghum putih dan P3 = tepung tapioca 0% + 15% tepung sorghum putih. Hasil penelitian secara statistik menunjukkan bahwa penggunaan tepung sorghum putih sebagai pengganti sebagian tepung tapioka tidak berpengaruh nyata (P>0,05) terhadap kandungan lemak tetapi berpengaruh sangat nyata (P<0,01) terhadap tingkat oksidasi lemak , kandungan antioksidan, warna dan rasa dari sosis itik Manila. Kesimpulan penggantian tepung tapioka dengan tepung sorghum putih sebesar 10-15% menyebabkan penurunan tingkat oksidasi lemak, sedangkan kandungan lemak tidak berubah dan antioksidan terjadi peningkatan pada sosis itik Manila. Nilai kandungan lemak berkisar dari 1.36±0.12 -1.81±0.27%, oksidasi lemak 5.98±0.79- 3.49±0.45 (mg.eq/kg), antioksidan 7.72±2.53-36.66±1.54 %, warna 5.00±0 - 1.83±0.91 dan rasa 2.00±0 - 2.97±0.77. Dari aspek penelitian organoleptik penggantian sebagian tepung sorghum putih dengan tepung tapioka hingga 15% menyebabkan warna sosis berubah menjadi berwarna abu-abu kehitaman dan rasa sosis meningkat di banding dengan kontrol.